EFL Students’ Perceptions on Using Edmodo in Online Learning During Covid-19 Pandemic - Bayu Ren Warin; Navi Rahmansyah; Reza Pradana (Celebes Scholar pg, 2022)
Covid-19 pandemic has been spread out in the entire world in 2020. Many aspects of life get the impact directly. In education, there are several impacts that must be face toward the situation, one of them is about the implementation online class in this new era. From kindergarten until university have their own ways to provide an online class effectively. The research has aim to give the perceptions from EFL students’ on using Edmodo in Critical Discourse Analysis online class. The researcher will give their point of view about this case also. This research will conduct 31 EFL students’, especially in Critical Discourse Analysis class, point of view about online class during pandemic Covid-19, they are from seventh semester in State Islamic Institute of Kediri. The results of the research are expected to provide the data from students’ perceptions about online class and how should this be, in order to improve the online class implementation in the further.